Análise da toxicidade in vivo de um triterpeno semissintético (CL-P2) e atividade antirreabsortiva de um hidrogel de sistema de liberação de CL-P2 no modelo de periodontite em camundongas wiss - Santos, Erika Vanessa Farias dos (2024)
INTRODUCTION: Combretum leprosum is a species popularly used in Brazil as an anti inflammatory agent. Phytochemical studies in the genus Combretum have demonstrated the presence of several classes of bioactive compounds, including the triterpene 3β,6β,16β-trihydroxylup-20(29)-ene (CL-1). OBJECTIVE: To evaluate the in vivo toxicity of the compound CL-P2, a semisynthetic triterpene obtained from CL-1, and the antiresorptive activity of a CL-P2 delivery system hydrogel in the periodontitis model in Swiss mice. The project was approved by CEUA-UFC Sobral (01/20). METHODS: Toxicity tests were performed using the Oral Toxicity protocol (OECD no. 425). For this, female Swiss mice (n=10) from the Central Bioterium of the Federal University of Ceará were used. The experimental groups included: Control (saline) and treatment with CL-P2 (175, 550 and 2000 mg/kg). Behavioral parameters were evaluated for 14 days. On the 15th day after euthanasia, blood was collected for analysis of uric acid, creatinine, ALT and AST levels. Organs were collected for histopathological analysis (H&E). Forty-eight female Swiss mice were used for the periodontitis assay. Periodontitis was induced by cotton thread (5.0) in the first lower molars. The groups included: naïve; periodontitis+vehicle hydrogel; periodontitis+CL-P2 hydrogel (1 or 10mg), applied 2x/d/14d. On the 15th day, the animals were euthanized and the hemiarches were collected for morphometric and histometric analyses (ImageJ® software) of the alveolar bone. Peripheral blood was collected for measurement of bone alkaline phosphatase (BAP). Ovaries were also collected to analyze the preclinical safety of the CL-P2 hydrogel on reproductive health. The Shapiro-Wilk test and ANOVA (Tukey) were used for statistical analysis, considering p<0.05 as significant. RESULTS: No mortality was observed during the 14 days of the test. In the behavioral analysis, an increase in the number of licks and drowsiness was observed at the beginning of treatment with CL-P2, with no significant changes in other parameters, such as body weight, liver and kidney functions and reproductive system. The hydrogel with CL-P2 10 mg/kg reduced alveolar bone loss with increased BAP levels. The use of the hydrogel did not negatively impact the survival and development of ovarian follicles, suggesting the safety of the compound on the reproductive health of mice. CONCLUSION: CL-P2 may represent a product with biotechnological potential for the production of a new antiresorptive drug.